Oxygen Increases Lung Inflammatory Response in Spontaneous One-Lung Ventilation in Rabbits: A Prospective Randomized Experimental Study - Machado, Humberto S. (2014)
Study objective: The purpose of this study was to investigate if oxygen supplementation would increase lung inflammatory response in a spontaneous one-lung ventilation animal model, when compared to room-air oxygen fraction. Design: In vivo prospective randomized animal study Setting: University research laboratory Subjects: New Zealand rabbits Interventions: Rabbits (n=20) were randomly assigned to 2 groups (n=10 each group). Groups (OS – Oxygen Supplemented, and NOS – Non-Oxygen Supplemented) were submitted to spontaneous One-Lung Ventilation (OLV) during 60 minutes; OS group had a 2-liter/minute oxygen supplement, and NOS group was kept on roomair. Ketamine/xylazine was administered for induction and maintenance of anesthesia. One-lung ventilation was achieved by administration of air into interpleural space, and left lung collapse was visually confirmed through the center of diaphragm. Clinical monitoring and arterial blood gas analyses were performed in all rabbits. Measurements: Lung histology plates were observed under light microscopy for quantification of inflammatory response (light, moderate and severe). Main results: All subjects had at least light inflammatory response. However, rabbits submitted to oxygen supplementation had a statistically significant value for the occurrence of moderate inflammation (p<0.001). The inflammatory cells found were mainly eosinophils and neutrophils in an average proportion of 80/20. Oxygen partial pressure increased in both groups with a higher proportion in OS group (p<0.001). Conclusion: In this spontaneous OLV model, the use of oxygen supplementation was associated with a greater inflammatory response.